2014
DOI: 10.1021/es405602a
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation Mechanism of Potassium on the V2O5/CeO2 Catalysts for SCR Reaction: Acidity, Reducibility and Adsorbed-NOx

Abstract: A series of V2O5/CeO2 catalysts with different potassium loadings were prepared to investigate alkali deactivations for selective catalytic reduction of NOx with NH3. An alkali poisoning mechanism could be attributed to surface acidity, reducibility, and NOx adsorption/desorption behaviors. The detailed factors are as follows: (1) decrease of surface acidity suppresses NH3 adsorption by strong bonding of alkali to vanadia (major factor); (2) low reducibility prohibits NH3 activation and NO oxidation by formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 28 publications
3
80
0
1
Order By: Relevance
“…Another new peak centered at 293°C appeared for LSM3 and grew considerably for LSM4. The total NO x desorption significantly decreased 38,39 In comparison to the peaks for LSM4 and LSM3, the intensity of the low temperature NO peak increased significantly. Previous work on a comparative study on α-Mn 2 O 3 and β-MnO 2 obtained similar TPR peaks at approximately 300°C on pure β-MnO 2 material.…”
Section: View Article Onlinementioning
confidence: 90%
“…Another new peak centered at 293°C appeared for LSM3 and grew considerably for LSM4. The total NO x desorption significantly decreased 38,39 In comparison to the peaks for LSM4 and LSM3, the intensity of the low temperature NO peak increased significantly. Previous work on a comparative study on α-Mn 2 O 3 and β-MnO 2 obtained similar TPR peaks at approximately 300°C on pure β-MnO 2 material.…”
Section: View Article Onlinementioning
confidence: 90%
“…From the above catalytic test results, we could conclude that the WO 3 species could improve the SCR catalytic reaction for CeO 2 /TiO 2 catalyst and the CeO 2 -WO 3 /TiO 2 catalyst had high catalytic activity, especially at low-temperature. 3 were not observed. It indicated that TiO 2 consisted of anatase as the unique phase and WO 3 species were well-dispersed over the support by calcination at 500°C.…”
Section: Characterizationmentioning
confidence: 82%
“…CeO 2 and WO 3 of CeO 2 -WO 3 /TiO 2 had strong hybridization between the orbitals of W5d and Ce5d. The interaction decreased the level of the CB bottom and VB top of CeO 2 in CeWTi catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective catalytic reduction (SCR) of NO with NH 3 over supported V 2 O 5 catalysts is efficient for controlling NO emissions from coal‐fired power plants,, but it is different to be applied in industrial glass and cement boilers, steel furnaces, and bio‐fueled boilers, because high‐concentration alkali metal ions in the stack gases often lead to severe deactivation of such SCR catalysts . Thus, it is desirable to develop SCR catalysts with strong resistance against alkali poisoning for controlling NO emissions especially in China, because some related regulations have been increasingly stringent.…”
Section: Introductionmentioning
confidence: 99%